2003
DOI: 10.1128/mcb.23.24.8925-8933.2003
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of 48S Translation Initiation Complexesfrom Purified Components with mRNAs That Have Some Base Pairingwithin Their 5′ UntranslatedRegions

Abstract: The reconstitution of translation initiation complexes from purified components is a reliable approach to determine the complete set of essential canonical initiation factors and auxiliary proteins required for the 40S ribosomal subunit to locate the initiation codon on individual mRNAs. Until now, it has been successful mostly for formation of 48S translation initiation complexes with viral IRES elements. Among cap-dependent mRNAs, only globin mRNAs and transcripts with artificial 5 leaders were amenable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 35 publications
11
82
0
Order By: Relevance
“…As seen from Fig. 3 (lanes 1 to 4), such complexes did form, and in the presence of initiation factors 1A, 2, 3, 4A, and 4F (eIF4B was not used in the assembly, since it is required only for mRNAs with structured 5Ј-UTRs [6]), their assembly occurred more efficiently than with 80S ternary complexes (compare lanes 2 and 8). The stimulatory effect of eIF4F (in the absence of eIF1) on the binding of uncapped, leaderless, and single-stranded cI mRNAs with the 40S ribosomal subunit was surprising.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…As seen from Fig. 3 (lanes 1 to 4), such complexes did form, and in the presence of initiation factors 1A, 2, 3, 4A, and 4F (eIF4B was not used in the assembly, since it is required only for mRNAs with structured 5Ј-UTRs [6]), their assembly occurred more efficiently than with 80S ternary complexes (compare lanes 2 and 8). The stimulatory effect of eIF4F (in the absence of eIF1) on the binding of uncapped, leaderless, and single-stranded cI mRNAs with the 40S ribosomal subunit was surprising.…”
Section: Resultsmentioning
confidence: 86%
“…The reconstitution of 48S complexes from purified components and their analysis by toeprinting were performed as described previously (5,6,16,17). For the assembly and toeprinting analysis of 80S translation initiation complexes, the reaction mixture (20 l) contained 80S reassociated ribosomes (2.5 pmol), an mRNA (0.5 pmol), MettRNA i Met (5 pmol), and, where indicated, the initiation factors at the same molar ratio as for the assembly and analysis of 48S translation initiation complexes (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Translational repression via the catalytic activity of eIF4A would selectively target mRNAs with 5Ј UTR structural content that rely on unwinding for efficient initiation (18,20,43,61). Using differential IRES analysis, it has previously been shown that BC1 RNA is not effective in repressing translation initiation of mRNAs that do not require unwinding of 5Ј UTR secondary structure by eIF4A (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…24 Yeast eIF4B preferentially stimulates translation from mRNAs with moderately stable secondary structure in the 5 0 UTR while it stimulates the higher basal level of translation from mRNAs that lack secondary structure only moderately. 54 Formation of a 48 S translation initiation complex (i.e., the binding of a 40 S subunit to an mRNA) with animal mRNAs containing a structured 5 0 UTR was dependent on eIF4B, 55 suggesting that, although the ability of eIF4B to promote eIF4A helicase activity is likely involved in the translation of mRNAs in general, it may be of particular importance for certain types of mRNAs.…”
Section: Plants Express a Novel Eif4g Isoform Not Found In Other Eukamentioning
confidence: 99%